Biodynamic lighting conditions preserve nocturnal melatonin production in pregnant women during hospitalization: A randomized prospective pilot study - Bagci, Soyhan; Wieduwilt, Astrid; Alsat, Ebru Aileen; Blickwedel, Jana; Strizek, Brigitte; Di Battista, Christian; Lachner, Agnes; Plischke, Herbert; Melaku, Tamene; Müller, Andreas (Frontiers in Endocrinology, 2022)
Background and purpose: Maternal circadian rhythms are important for maintaining maternal and fetal homeostasis. The maternal circadian system coordinates the internal clock of the fetus with environmental lighting conditions via the melatonin signal. The intensity and wavelength of daylight influence nocturnal melatonin production. This study aims to evaluate the effect of environmental lighting conditions on melatonin production in pregnant women with reduced mobility during hospitalization. Methods: We installed a human-centric lighting system with biodynamic effects (BDL, biodynamic lighting) in the patient rooms. The pregnant women in the patient rooms with standard indoor conditions served as a control group. The illuminance (lux) and dose of effective circadian irradiation (Hec) were recorded every 10 seconds by light dosimeters (Lucerne University, Switzerland) attached to the patients` clothing. Results: We analyzed the illuminance status of 47 pregnant women with a median (IQR) gestational age of 29.9 (25.4-32.3) weeks of gestation. The median illuminance in the control group was significantly lower (p<0.05) than in the BDL group in the morning and afternoon from day 1 to 5. BDL patients had a significantly higher effective circadian irradiation in the morning. The effective circadian irradiation showed a significant daily rhythm only in the BDL group. The BDL group had a significantly higher melatonin production on day 3 (p=0.006) and day 6 (p=0.012) than the control group (median (IQR) 15840 (10140-22160) ng vs. 6141 (2080-11328) ng/n on day 3 and 18780 (11320-23562) ng vs. 6380 (3500-17600) ng on day 6). Conclusion: We have demonstrated that dramatically altered lighting conditions of hospitalized pregnant women may be optimized by installing biodynamic lighting systems in the patient rooms resulting in the maintenance of nocturnal melatonin production in pregnant women.